Robbie McNeil's hit list - Heath, Brianna (Poisoned Pen Press, an imprint of Sourcebooks, 2026)
"Contract killer Robbie McNeil never asks questions. Her mission is simple. Do the job. Get paid. Get back to running the karaoke bar she co-owns with her queerplatonic partner and fellow contract killer, Dee. And it works... Until their ambitious new theatrical venture breaks the bank. When a mysterious new client hires Robbie for a hit, she takes the job, even though it's sketchy as hell he won't tell her anything but the target's name. But hey, she didn't build her reputation by being curious, and she desperately needs the cash. Except something about this new target doesn't add up. When he disappears with no record he ever existed, she chucks her no-questions-asked policy out the window, determined to figure out who this target really is. But the price for asking questions is high and might just cost Robbie everything she holds dear"--